PELATIHAN LITERASI MEDIA DAN KEUANGAN DIGITAL UNTUK MENINGKATKAN KOMPETENSI GURU SD NEGERI DI TIGARAKSA BANTEN - Lisa Esti Puji Hartanti; Rosdiana Sijabat; Paskalia (Jurnal Bakti Masyarakat Indonesia, 2025)
Significant advancements in technology have necessitated that the educational sector perpetually enhance its competencies, particularly among teaching professionals. Teachers are regarded as role models for students and are expected to develop their competencies in the digital domain. Digital literacy is defined as the ability to use digital technologies to access information, communicate, and solve problems. The necessary skills include the use of computers or digital device and the internet, as well as the participation in online communication. To enhance digital literacy, a collaborative effort has been initiated by a team of lecturers and students from the Faculty of Business and Communication Sciences, Atma Jaya Catholic University of Indonesia. This initiative involves the provision of training on digital literacy to 38 teachers at public elementary schools in Tigaraksa, Banten. The digital literacy training component of the activities encompasses both media literacy and digital financial literacy. The digital media literacy training encompasses education on the subject of fake news, the process of fact-checking, and the practice of critical reading. The digital financial literacy training programme encompasses the fundamental principles of the subject, the various categories of digital financial crime, and the methodologies employed to anticipate such criminal activities. The PKM method is implemented by providing materials, facilitating discussions, and organising practice sessions, in addition to conducting surveys before and after the training period. The activity encompasses the stages of preparation, implementation, support, monitoring, and evaluation. The outcome of this activity is that participants have expanded their knowledge of digital media and finance literacy, especially those with large knowledge gaps regarding fact-checking platforms (M = -1.69) and ways to combat digital financial crime (M = -1.51). Furthermore, recommendations for the future of the programs include the expansion of topics where there are significant gaps and the implementation of regular, continuous training. This pedagogical approach is designed to facilitate the acquisition of knowledge and the reception of guidance by the participants. It is hoped that participants will apply the knowledge they have acquired and that there will be room for discussion as a form of monitoring.   ABSTRAK Perkembangan teknologi yang masif, membuat dunia pendidikan perlu untuk terus meningkatkan kemampuan, khususnya bagi pengajar atau guru. Guru sebagai role model peserta didik diharapkan mampu meningkatkan kompetensi diri dalam dunia digital. Literasi digital merupakan kemampuan menggunakan teknologi digital untuk mengakses informasi, berkomunikasi, dan memecahkan masalah. Keterampilan yang perlu dimiliki adalah menggunakan komputer atau perangkat digital, internet, dan berpartisipasi dalam komunikasi online. Maka, untuk meningkatkan kemampuan literasi digital, tim dosen dan mahasiswa dari Fakultas Ilmu Administrasi Bisnis dan Ilmu Komunikasi Universitas Katolik Indonesia (Unika) Atma Jaya memberikan edukasi berupa pelatihan literasi digital kepada 38 Guru Sekolah Dasar Negeri di Tigaraksa, Banten. Edukasi literasi digital yang diberikan dalam program Pengabdian Kepada Masyarakat (PKM) ini adalah literasi media dan keuangan digital. Pelatihan literasi media digital meliputi, pengetahuan tentang hoaks, cek facta, dan membaca kritis. Pelatihan literasi keuangan digital meliputi, pengetahuan dasar, jenis kejahatan keuangan digital dan cara mengantisipasinya. Metode pelaksanaan PKM dengan memberikan materi, diskusi, praktik, serta memberikan survei sebelum dan setelah pelatihan. Tahapan kegiatan meliputi persiapan, pelaksanaan dan pendampingan, serta monitoring dan evaluasi. Hasil dari PKM ini adalah para peserta mengalami peningkatan pengetahuan terkait literasi media dan keuangan digital, khususnya yang memiliki gap besar adalah platform cek fakta (M = -1,69) dan cara mengatasi kejahatan keuangan digital (M = -1,51). Lalu, saran untuk PKM selanjutnya dapat memperdalam topik tersebut, serta, melaksanakan pelatihan tidak hanya dalam satu waktu, tetapi berjangka dan berkelanjutan. Sehingga, peserta mendapatkan pengetahuan dan juga pemantauan. Maka, harapannya peserta menerapkan pengetahuan yang didapat dan ada ruang untuk diskusi sebagai bentuk monitoring.